Treatability study for industrial wastewater by using lateric soil as coagulant - Nurasyikin Yaacof (Penerbit Universiti Malaysia Perlis, 2011)
Coagulant and flocculant are the important process in the industrial wastewater treatment plant. This is because, through this process, total suspended solid and other material in the wastewater can be settle and remove. The common problem that had been usually face during the process is to remove colour or dyes in the wastewater. Each dye has its own chemical structure and bonding, to remove the dyes industry usually used chemical coagulant aid as the coagulant agent. There are various types of chemical coagulant aids in the industries such as Aluminium Chloride and Polyaluminium Chloride (PAC). Its capability can not be denied but the problem is chemical coagulant aid will give side effect on environmental and human health. Chemical coagulant will produce harmful chemical sludge which is hard to degrade. Furthermore, there is a possible link of Alzheimers disease with conventional aluminium based coagulants. The purpose of this study is to figure our whether red soil have the ability to be the coagulant aid or not. In the other word, this alternative is call as natural biocoagulant. Before this natural biocoagulant can be use, there are various test must be run. There are to find the optimum pH, concentration and optimum dosage for the coagulant aid. This is important to maintain and safe the cost of the industrial wastewater treatment plant and to have the satisfied performance of the wastewater treatment. In coagulant and flocculant process, pH and dosage are the important factor. Not all dye can be removed by using same pH and dosage, this is because of the different characteristic and structure of the dyes. For methylene blue, the optimum dosage is 15ml and its optimum concentration is 25%, reactive black is 21ml and in 55% concentration and for mix dyes is 11ml in 25% concentration. From the test to find the optimum pH, it has been discover that the optimum pH for all dyes is at its original pH which is between 7-8. With this, the usage of chemical to adjust pH can be avoid and less chemical will be use in the treatment.